Improve Household Income Through Peking Duck Farming - Amir Hamzah; Hesti Umiyati; RR Prima Dita Hapsari; Arvadi Hutagalung; Paula Theodora; Risa Ristiani; Ubaidillah; Dwi Okty Utami (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: Community service was carried out to increase household income in the Serdang village, Curug district, Tangerang regency, by breeding and rearing Peking ducks. Contribution: Peking duck breeding and rearing farming is considered relatively low in maintenance, attainable ducklings, and affordable feed; while the problem of Peking duck breeding and rearing farming is the lack of capital. Method: The implementation methods consist of: the planning stage, the implementation stage, and the evaluation stage. Results: The result of this community service is the achievement of total 2,597.9 Kg of ready-to-sell Peking ducks, with the sales profit of Rp 17.950.750 per month. From the total of 1,100 heads initial ducklings reared the mortality rate of 91 occurred at the vulnerable age (5-15 days). Conclusion: By the end of the second season of community service, 3 (three) participants become self-suffcient Peking duck breeders